2021
DOI: 10.1007/s11356-021-14961-9
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction among medical and non-medical students during COVID-19 pandemic, Tanta University, Egypt

Abstract: Internet addiction is one of the most growing addictive behaviors worldwide, especially among university students affecting their physical and mental health negatively. During COVID-19, accessing online books, completing assignments, and online assessments are highly recommended by universities, teachers, and students. The Internet has increasingly become a vital part of our lives, and distant online classes increase the dependency of students on the Internet. The aim of this study is to assess the level of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…The present study did not find a difference in the IA prevalence considering the participants’ faculty subject area, which is in concordance with an earlier study among Croatian university students [ 35 ] and a recent study among Indian students [ 33 ], although a recent study from Egypt found that students who studied in the field of biomedicine a more prone to IA development [ 47 ] and study among Indian students published in 2020 showed that students who studied in the field of technical sciences are the most vulnerable for the development of IA [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…The present study did not find a difference in the IA prevalence considering the participants’ faculty subject area, which is in concordance with an earlier study among Croatian university students [ 35 ] and a recent study among Indian students [ 33 ], although a recent study from Egypt found that students who studied in the field of biomedicine a more prone to IA development [ 47 ] and study among Indian students published in 2020 showed that students who studied in the field of technical sciences are the most vulnerable for the development of IA [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this context, social norms, socio-cultural attitudes, but also a lower digital participation of females may play an important role in terms of protective factors ( 78 ). However, there is also evidence of female susceptibility to internet addiction ( 79 ). A possible explanation for this is the pandemic itself, which may have erased male dominance in terms of internet addiction ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…h 1 = Less than 6 hours, 2 = 6 to 7 hours, 3 = More than 7 hours; I 1 = Less than 2 hours, 2 = 2 to 3 hours a greater risk of internet addiction across different cohorts. [34][35][36] One study reported that the prevalence of severe internet dependence rose 23% during COVID-19 pandemic. 33 Table 4 provides a comparison of results in the present study with online use behaviors in previous Bangladeshi studies assessing similar variables.…”
Section: Discussionmentioning
confidence: 99%